EDUCATION, FINANCIAL LITERACY AND PLANNING ON MSMES FINANCIAL BEHAVIOR IN CIREBON CITY - Ida Rosnidah; Kartono; Evi Lativah (UPT Publikasi Ilmiah UNISBA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an economic sector that plays a strategic role in promoting growth and equitable economic development, particularly at the regional level. This study aims to analyze the influence of education level and financial literacy on the financial behavior of MSME actors in the City of Cirebon, as well as to examine the role of financial planning as a mediating variable in this relationship. The research employs a descriptive quantitative method with an explanatory research approach. The researcher used a simple random sampling technique and determined the sample size using the Slovin formula, resulting in a total of 187 MSME respondents. Data analysis was conducted using the Partial Least Square – Structural Equation Modeling (PLS-SEM) technique through the SmartPLS 3 software. The results indicate that both education level and financial literacy have a positive influence on financial planning and financial behavior. Moreover, financial planning significantly affects financial behavior and is capable of mediating the influence of education level and financial literacy on financial behavior. These findings highlight the importance for MSME actors to improve their education level and financial literacy in order to enhance financial planning and financial behavior.